Nonthyroidal illness syndrome as independent predictor of hospital mortality in the elderly hospitalized patients with COVID-19 pneumonia – single-center observation - Młodożeniec, Aleksandra; Orłowska-Florek, Renata; Czarnożycka-Wróbel, Adrianna; Gargasz, Krzysztof; Gala-Błądzińska, Agnieszka (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Elderly patients with COVID-19 are at increased risk for adverse outcomes. This study aims to evaluate the prevalence of nonthyroidal illness syndrome (NTIS) in hospitalized patients with COVID-19 pneumonia, its independent impact on patients’ survival. Furthermore, to investigate selected inflammatory biomarkers in those patients and to determine whether they predict mortality associated with the disease. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this single-centered, retrospective study, the medical records of 53 patients with confirmed SARS-CoV-2 infection who attended the provincial hospital between October 2020 and January 2021 were reviewed. Demographic data, laboratory values, comorbidities, treatments, and clinical outcomes were collected. We compared the data in survivor and non-survivor groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Of 393 adult patients with SARS-CoV-2 pneumonia, 53 (13,49%) met the inclusion criteria and were included. The median age was 72±12.2 years, 26 patients (49%) were men. The NTIS prevalence was 62.3% and showed a strong independent correlation with disease severity and mortality in COVID-19 patients (p=0.01). The interleukin-6, white blood cells, ferritin and neutrophil ratios also differed significantly statistically between survivors and non-survivors. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. NTIS and the lowering level of FT3 pose an independent prognostic marker of clinical deterioration and higher mortality in elderly patients with COVID-19.